ARR17 controls dioecy in Populus by repressing B-class MADS-box gene expression. (9th May 2022) - Leite Montalvão, Ana P.; Kersten, Birgit; Kim, Gihwan; Fladung, Matthias; Müller, Niels A.
Abstract : The number of dioecious species for which the genetic basis of sex determination has been resolved is rapidly increasing. Nevertheless, the molecular mechanisms downstream of the sex determinants remain largely elusive. Here, by RNA-sequencing early-flowering isogenic aspen ( Populus tremula ) lines differing exclusively for the sex switch gene ARR17, we show that a narrowly defined genetic network controls differential development of female and male flowers. Although ARR17 encodes a type-A response regulator supposedly involved in cytokinin (CK) hormone signalling, clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9-mediated arr17 knockout only affected the expression of a strikingly small number of genes, indicating a specific role in the regulation of floral development rather than a generic function in hormone signalling. Notably, the UNUSUAL FLORAL ORGANS ( UFO ) gene, encoding an F-box protein acting as a transcriptional cofactor with LEAFY ( LFY ) to activate B-class MADS-box gene expression, and the B-class gene PISTILLATA ( PI ), necessary for male floral organ development, were strongly de-repressed in the arr17 CRISPR mutants. Our data highlight a CK-independent role of the poplar response regulator ARR17 and further emphasize the minimal differences between female and male individuals. This article is part of the theme issue 'Sex determination and sex chromosome evolution in land plants'.